2018
DOI: 10.3233/prm-180534
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing pediatric pain and agitation during botulinum toxin injections for spasticity with virtual reality: Lessons learned from clinical use

Abstract: VR was helpful in reducing BoNT procedure-related discomfort in a majority of patients. Challenges with VR setup, patient tolerance, and selecting viewing experiences were identified to guide further research and use of VR in a clinical environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…A number of clinical studies have demonstrated the benefit of VR distraction analgesia, including wound-dressing changes for burn patients, 6,11-20 venipuncture, 21-28 chemotherapy administration, 29 cystoscopy and urologic surgery, 2,30 episiotomy repair, 31 injections, 32,33 lumbar punctures, 34 and dental procedures. 35 A recent meta-analysis of VR use in acute procedural pain management supported its incorporation as nonpharmacologic analgesia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of clinical studies have demonstrated the benefit of VR distraction analgesia, including wound-dressing changes for burn patients, 6,11-20 venipuncture, 21-28 chemotherapy administration, 29 cystoscopy and urologic surgery, 2,30 episiotomy repair, 31 injections, 32,33 lumbar punctures, 34 and dental procedures. 35 A recent meta-analysis of VR use in acute procedural pain management supported its incorporation as nonpharmacologic analgesia.…”
mentioning
confidence: 99%
“…administration, 29 cystoscopy and urologic surgery, 2,30 episiotomy repair, 31 injections, 32,33 lumbar punctures, 34 and dental procedures. 35 A recent meta-analysis of VR use in acute procedural pain management supported its incorporation as nonpharmacologic analgesia.…”
mentioning
confidence: 99%
“…A total of 18 studies were deemed suitable for inclusion in this review [17][18][19][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The article selection process is outlined in Figure 1.…”
Section: General Description Of Studiesmentioning
confidence: 99%
“…The descriptive data collated from the eligible studies are reported in Table S1 (Multimedia Appendix 1). All 18 studies were conducted and published between 2004 and 2018: 50% (9/18) of studies were specifically focused on the pediatric population; 72% (13/18) of studies compared virtual reality against standard analgesia as the comparator/control group [18,19,26,[29][30][31][32][33][34][35][36]38,39]; 28% (5/18) of studies compared virtual reality to no analgesia [17,25,27,28,37]. Overall, only 1 study of 18 (6%) received a bias assessment score less than 7 out of 10.…”
Section: General Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation